Predictive value and changes of inducible nitric oxide synthase expression in patients with rectal cancer under the influence of antitumor therapy - V. V. Holotiuk; A. Ye. Kryzhanivska; I. Ya. Sadovyi; B. B. Tataryn (Patologìâ)
The aim of investigation – to establish the features of iNOS expression in the rectum wall under the influence of various neoadjuvant therapy options in patients with rectal cancer (RC) and to find out its predictive significance.